Complex Surgical Treatment of an Open Fracture of the Distal End of the Shin Bones (Literature Review) (Texas Journal of Medical Science, 2022)
Treatment of fractures of the shin bones remains one of the most important problems not only in traumatology, but also in a number of related specialties. The duration of treatment of victims varies widely: from 3-4 months with closed tibial fractures without displacement to 5-7 months in cases of open injuries. With complicated fractures, they often reach 9-10 months or more. In the structure of disability, fractures of the lower leg occupy a leading place and account for 7.0–37.6% of all injuries of the musculoskeletal system.